Pengaruh Self Regulated Learning dan Self Efficacy terhadap Prestasi Akademik Mahasiswa - Yowelna Tarumasely (Jurnal Pendidikan Edutama, 2021)
Abstract: This study aims to determine: the effect of self-regulated learning on student academic achievement, (2) the effect of Self Efficacy on academic achievement; (3) the influence of Self Regulated Learning and Self Efficacy on Academic achievement. The population in this study were 70 students in Semester II, the research sample as much as the population, namely 70 students. The method used is multiple linear regression analysis. The results showed that: (1) Self regulated learning had no effect on student academic achievement, (2). Self-efficacy has a significant effect on student academic achievement, and (3) Self regulated learning and Self-efficacy simultaneously affect student academic achievement. Keywords: Self Regulated Learning, Self Efficacy, Academic Achievement Abstrak: Penelitian ini bertujuan untuk mengetahui: pengaruh self regulated learning terhadap prestasi akademik mahasiswa, (2) pengaruh Self Efficacy terhadap prestasi Akademik; (3) pengaruh Self Regulated Learning dan Self Efficacy terhadap prestasi Akademik. Populasi dalam penelitian ini adalah Mahasiswa Semester II sebanyak 70 mahasiswa, sampel penelitian sebanyak jumlah populasi yakni 70 mahasiswa. Metode yang digunakan adalah analisis regresi linear berganda. Hasil penelitian menunjukkan bahwa: (1) Self regulated learning tidak berpengaruh terhadap prestasi akademik mahasiswa, (2). Self efficacy secara signifikan berpengaruh terhadap prestasi akademik mahasiswa, dan (3). Self regulated learning dan Self efficacy secara simultan berpengaruh terhadap prestasi akademik mahasiswa. Kata Kunci: Self Regulated Learning, Self Efficacy, Prestasi Akademik